Preface: The Sacred and the Secular in Taoism: Theories, Practices, and Communities - Guo, Wu (Religions, 2024)
As an indigenous religion of China, Taoism has always been regarded as “Za Er Duoduan” 雜而多端 (Miscellaneous and Multifaceted), just as a famous scholar Ma Duanlin 馬端臨 (1254–1340) said in the Yuan dynasty (1271–1368) [...]